Advancing Herbal Medicine: The Role of Nanosomal Technology in Treating Skin Diseases - Aswan, Pedro Anugerah; Maggadani, Baitha Palanggatan; Fachri, Wilzar; Iswandana, Raditya (Pharmaceutical Sciences and Research, 2025)
Herbal medicine has become popular worldwide, especially in developing countries, with around 80% of the population opting for herbal treatments. The perceived benefits of natural remedies, such as affordability and fewer side effects, drive this trend. Herbal therapies effectively manage skin diseases, infections, and common ailments. However, the absorption of bioactive compounds in herbal extracts is often limited. Recent developments in nano-based herbal delivery systems, like nanosomal, show promise in enhancing the efficacy of herbal remedies for topical applications, providing improved solubility, stability, and skin penetration. This review describes various nanosomal studies developed and successfully used to enhance the topical delivery of natural compounds, including liposomes, ethosomes, transfersomes, transethosomes, phytosomes, and niosomes.